Textbooks- Hear our Voice! - Nawani, Disha (Voices of Teachers and Teacher Educators, 2017)
The paper, written in first person, personifies textbooks and traces the history of both their form and current use in India. It explains the difference and inter-linkages between curriculum, syllabus and textbooks. It also argues that prevailing problems pertaining to textbooks is because of the manner in which they are conceptualised, written and used and if these concerns are suitably addressed, they can genuinely serve as a very valuable pedagogic resource in school education.